Gender in medicine – an issue for women only? A survey of physician teachers' gender attitudes - Risberg, Gunilla (BioMed Central, 2003)
BACKGROUND: During the last decades research has disclosed gender differences and gender bias in different fields of academic and clinical medicine. Consequently, a gender perspective has been asked for in medical curricula and medical education. However, in reports about implementation attempts, difficulties and reluctance have been described. Since teachers are key persons when introducing new issues we surveyed physician teachers' attitudes towards the importance of gender in professional relations. We also analyzed if gender of the physician is related to these attitudes. METHOD: Questionnaires were sent to all 468 senior physicians (29 % women), at the clinical departments and in family medicine, engaged in educating medical students at a Swedish university. They were asked to rate, on five visual analogue scales, the importance of physician and patient gender in consultation, of physician and student gender in clinical tutoring, and of physician gender in other professional encounters. Differences between women and men were estimated by chi-2 tests and multivariate logistic regression analyses. RESULTS: The response rate was 65 %. The physicians rated gender more important in consultation than in clinical tutoring. There were significant differences between women and men in all investigated areas also when adjusting for speciality, age, academic degree and years in the profession. A higher proportion of women than men assessed gender as important in professional relationships. Those who assessed very low were all men while both men and women were represented among those with high ratings. CONCLUSIONS: To implement a gender perspective in medical education it is necessary that both male and female teachers participate and embrace gender aspects as important. To facilitate implementation and to convince those who are indifferent, this study indicates that special efforts are needed to motivate men. We suggest that men with an interest in gender issues should be involved in this work. Further research is needed to find out how such male-oriented endeavours should be outlined.